2003
DOI: 10.1099/vir.0.19029-0
|View full text |Cite
|
Sign up to set email alerts
|

An immunostimulatory oligodeoxynucleotide containing a cytidine-guanosine motif protects senescence-accelerated mice from lethal influenza virus by augmenting the T helper type 1 response

Abstract: The SAM-P1 strain of senescence-accelerated model mice shows an impaired T helper type 1 (Th1) immune response upon infection with influenza virus, which results in high susceptibility to the virus. Treatment of spleen cells from SAM-P1 mice with an immunostimulatory oligodeoxynucleotide containing a cytidine-guanosine motif (CpG ODN) in vitro increased the ratio of the titre of IFN-c to that of IL-4. Administration of CpG ODN to SAM-P1 mice generated satisfactory virus-specific cytotoxic T-lymphocyte response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…In addition, recent studies show that systemic administration of CpG ODN improved recovery of mice infected with the Friend leukemia virus and senescent mice infected with the influenza virus (12,44). Protection in all cases was linked to induction of a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies show that systemic administration of CpG ODN improved recovery of mice infected with the Friend leukemia virus and senescent mice infected with the influenza virus (12,44). Protection in all cases was linked to induction of a Th1 response.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have shown that the CpG-DNA has an outstanding immunostimulatory activity for inducing a strong Th1 immune response, resulting in induction of Th1 cytokines such as IL-12, IFN-α and IFN-γ (3)(4)(5). The enhanced Th1 responses contribute to the protection of the host from infectious agents (6). CpG-DNA also improves antigenpresenting cell activity through upregulation of major histocompatibility (MHC) class II molecules and costimulatory molecules (CD40, CD80, and CD86) (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…CpG treatment results in potent Th1 cytokine expression (IFNs and interleukin-12 ), activation of dendritic cells (DCs), NK cells, and B cells, and induction of Th1 cells and a Th1 antibody profile (30,35,83). CpG has been extensively studied in animal models of systemic and pulmonary infectious diseases caused by influenza virus (15,82) and other bacterial, fungal, and parasitic pathogens (3,9,15,17,25,34,51,77). Bacterially derived ADP-ribosylating enterotoxins, including CT from Vibrio cholerae and LT from E. coli, are robust systemic and mucosal adjuvants.…”
mentioning
confidence: 99%
“…The first strategy has been demonstrated in animal models by administering host proteins/glycoproteins that function in immune defense, such as the pattern recognition receptor (PRR) mindin (28), milk-derived glycoproteins (61), and virally delivered interferon (IFN) cytokines (27). Immunomodifiers of microbial origin have also been used to enhance host response to infection, including the binding subunit of cholera toxin (CT-B) (49), Th1-promoting Toll-like receptor (TLR) agonists CpG oligodeoxynucleotides (ODN) (15,82), poly(I:C) (81), 3 M-011 (23), and synthetic lipid A analogs (11). Immunomodulators used in the second strategy, with the aim to prevent detrimental inflammation, have been associated with improved infection outcomes and include enterotoxin mutant LT(S63K) (80) and anti-inflammatory COX-2 inhibitors (84).…”
mentioning
confidence: 99%